The P2X7 Receptor as Regulator of T Cell Development and Function - Grassi, Fabio (Frontiers in Immunology, 2020)
Unique structural features characterize the P2X7 receptor with respect to other P2X family members. Dual gating by eATP and regulated expression of P2X7 can imprint distinct outcomes to the T cell depending on the metabolic fitness and/or developmental stage. In the thymus, signaling by P2X7 contributes to  T cell lineage choice. In secondary lymphoid organs, P2X7 stimulation promotes Th1/Th17 polarization of CD4+ naïve cells, Tregs conversion to Th17 cells and cell death of Tfh cells that are not stimulated by cognate antigen. Moreover, P2X7 stimulation in eATP rich microenvironments, such as damaged and/or inflamed tissues as well as tumours, induces cell death of various T cell effector subsets.